Metoda varnega predogleda sumljivih priponk PDF z zaklenjeno pretvorbo v slikovni zapis in e-poštnim agentom kot vmesnikom za uporabnika - Rojec, Žiga (Elektrotehniški vestnik, 2025)
PDF files can act as carriers of malicious code, reaching users’ email inboxes in the form of attachments. This paper proposes a novel method for a technical solution enabling the secure, fast, and simple viewing of PDF files from untrusted sources that may potentially contain malicious code. Using the statically linked Poppler library, a one-way local conversion of the PDF content into an image format (JPG) is performed. The conversion process is executed within a Seccomp sandbox located within an unprivileged Docker container, which protects the underlying operating system from the potential execution of malicious code during the document conversion. This design reduces the attack surface associated with the dynamic interpretation of the PDF structure and is suitable for integration into environments with limited security privileges. The conversion is exceptionally fast, as it eliminates the need for full system virtualization that would otherwise be required to achieve a similar level of security. In addition to a standalone implementation as a local CLI tool, the paper proposes an architecture for a cloud-based microservice with an email agent, which provides an intuitive and user-friendly interface at the level of simply sending an email message to the system agent. The paper includes a technical description of the implementation, an efficiency evaluation, and a comparison with classical virtualization-based approaches.
Keywords: cybersecurity; kibernetska varnost; kvantna komunikacija; kvantna tehnologija; kvantno razdeljevanje ključev; quantum communication; quantum key distribution; quantum technology; satelitska komunikacija; satellite communication; telecommunications; telekomunikacije